Manejo de pragas do feijoeiro (Phaseolus vulgaris, Linnaeus, 17S3) atraves da utilizacao de cobertura de solo associada a resistwncia varietal - Hohmann, C.L.; Schoonhoven, Aart van; Cardona, C. (1979)
An expt. to study the background soil effects associated with var. resistance in bean pest populations, virus incidence and yield was carried out at the Centro Internacional de Agricultura Tropical (CIAT), Palmira, Colombia from Jan.-March, 1978. The effect of the treatments and of the var. on Empoasca kraemeri populations of nymphs and adults was positive. The var. x treatment interaction was only significative for nymph populations. The treatment with Al foil was the most effective for the var. P 14 and Diacol-Calima. Considering the larval plant damage and Chrysomelidae populations it was observed that the background soil with rice mulching is attractive to insects. A virus complex was present, and it was not possible to clearly evaluate the effects of the treatments. The yielding of the var. Diacol-Calima was superior with the aluminium background and rice mulching. These treatments yielded 2.3 and 1.3 times more than the control, resp. Var. P 14 showed a major pest- and disease-tolerance. A significative influence of the nymphs and adults of E. kraemeri and of the virus incidence on the yields were indicated by the correlation analysis. Adults of Chrysomelidae did not affect the yield significantly. (AS)